ANALISIS METAPHOR PADA RATATOUILLE: PENDEKATAN SEMANTIK - Mutiara Indah; Asrul Mustaqim (STKIP Subang, 2022)
The research title is An Analysis of Metaphor In Ratatouille’s Movie: Semantic Approach. Semantics is generally designed as the study of meaning in semantics there is a figurative language that compares and exaggrate the word and the metaphor is part of figurative language. Metaphor is an understanding and experience of one kind of thing in terms of another, the conceptual metaphor classified as three part namely: structural metaphor, orientational metaphor, and ontological metaphor. The object of this research is Ratatouille’s movie. the objective of this research is describe type of metaphor (1) to know what the dominant metaphor in this movie (2) To find the meaning of metaphor, The study of this research is using descriptive qualitative with the researcher is the instrument itself. The data of this research is the utterance which contains metaphor. Then the writer classified and study find the meaning by using source and target domain. The result of this research shows that this research have three types of metaphor there are 8 structural metaphors, 16 orientational metaphors, and 23 ontological metaphors. In conclusion, the dominant metaphor is ontological metaphor because the character of this movie usually compares an object with a human motivation, activities, and characteristic, they also use a human as a container.